ANALISIS PELANGGARAN ETIKA PROFESI HUKUM ADVOKAT DI INDONESIA STUDI KASUS ADVOKAT ROY RENING DALAM PENANGANAN KASUS MANTAN GUBERNUR PAPUA - Witarti Rabawati , Dwityas; Silviana Dewi, Nataly; Samane, Kristiani; Pandong, Elfege Kotoen; Siwemole, Louose M. N. Artono (Gapenas Publisher, 2024)
The writing of this paper discusses violations of legal professional ethics committed by advocate Stefanus Roy Rening in his handling of the case of the former Governor of Papua, Lukas Enembe. The research method used in analyzing the problem of this violation case was normative where it was found that Roy Rening was suspected of being involved in acts of obstructing investigations by the Corruption Eradication Commission (KPK), including giving directions to witnesses not to comply with investigators' summons and creating scenarios to influence public opinion. This action not only violates the code of ethics of an advocate but also the law that regulates the eradication of criminal acts of corruption. The impact of this violation has the potential to damage public trust in the advocate profession and the legal system in Indonesia. To prevent similar violations in the future, it is recommended that the code of ethics be enforced, improve professional ethics education, as well as the establishment of an independent oversight body. In this way, it is hoped that the integrity and professionalism of advocates can be maintained and public trust in the legal system can be justified.